Handbook of electronic package design - Pecht, Michael (Mechanical engineering (Marcel Dekker, Inc.), 1991)
Handbook for practitioners and a text for use in teaching electronic packaging concepts, guidelines, and techniques. The treatment begins with an overview of the electronics design process and proceeds to examine the levels of electronic packaging and the fundamental issues in the development